Green synthesis of nickel oxide coupled copper hexacyanoferrate (NiO2–CuHCF) nanocomposites for efficient and highly stable natural sunlight-driven photocatalytic degradation of wastewater pollutants. Issue 18 (15th September 2022) - Shuaib, Urooj; Lee, Dongseong; Hussain, Tousif; Ahmad, Riaz; Hwang, Jaeseok; Imranullah, M.; Mubarik, Farrukh Ehtesham; Ahmed, Sajjad; Kang, Dae Joon; Shakir, Imran
Abstract: Metal hexacyanoferrates are found to be the promising candidates utilized to degrade toxic dyes from waste water under natural sunlight irradiation. Coupling of metal hexacyanoferrate with metal oxide enhances the degradation efficacy. In present work, nickel oxide coupled copper hexacyanoferrate nanocomposites (NiO2 –CuHCF) are synthesized by employing facile co-precipitation route. XRD reveals the incorporation of NiO2 with CuHCF. SEM confirms the sheet like structures of NiO2 –CuHCF nanocomposite. TEM demonstrates the even distribution of elements present in the NiO2 –CuHCF nanocomposite. XPS shows the active participation of constituents having different valence states. The UV–Vis (DRS) is employed to measure the optical properties. The band gap of nickel oxide coupled copper hexacyanoferrate nanocomposite (NiO2 –CuHCF) decreases in comparison with pure copper hexacyanoferrate (CuHCF) from 1.23 to 1.14 eV. 97% degradation of Methyl blue (MB) is observed in just 110 min by NiO2 –CuHCF nanocomposite when exposed to natural sunlight. Moreover, it also retains 92% photocatalytic efficiency over 6 cycles which shows its excellent stability and reusability. The improved photocatalytic performance of NiO2 –CuHCF nanocomposite is attributed to their sheet resembling morphologies which may provide adequate active sites responsible to transport more charge carriers and also reduce charge recombination. In general, this research may open new avenue to use CuHCF with the addition of NiO2 in future as an efficient degradation agent at industrial level.